Our Voices Mattered: Role Expectations of Black Employees in Helping Employers Create a Supportive Diversity Climate: A Retrospective View - Munchus, George; Edmondson, Vickie Cox (Journal of Marketing Development and Competitiveness, 2022)
The first two tenured Black American faculty members in a business school accredited by the Association to Advance Collegiate Schools of Business reflect on their efforts to help administrators and faculty further embrace diversity as a key component of its growth strategy and marketing plan. The authors assert that institutions of higher learning are in a unique position. Not only are these institutions expected to teach about the benefits of embracing diversity, but to also model behaviors that demonstrate they walk the talk, thereby enhancing the organization’s diversity climate. Change may not be immediate, but over time with deliberate practice, faculty and organizations should see marketable results. Seven suggestions are set forth to help employers create a supportive diversity climate.